2017
DOI: 10.15252/emmm.201607370
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Toxoplasma gondii CPSF 3 as a new approach to control toxoplasmosis

Abstract: Toxoplasma gondii is an important food and waterborne pathogen causing toxoplasmosis, a potentially severe disease in immunocompromised or congenitally infected humans. Available therapeutic agents are limited by suboptimal efficacy and frequent side effects that can lead to treatment discontinuation. Here we report that the benzoxaborole AN3661 had potent in vitro activity against T. gondii. Parasites selected to be resistant to AN3661 had mutations in TgCPSF3, which encodes a homologue of cleavage and polyad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 34 publications
3
80
0
Order By: Relevance
“…This class of imidazopyrazines inhibits phosphatidylinositol 4 kinase (PI4K) in Plasmodium falciparum (12), an activity that may explain its potent ability to control C. parvum growth in vitro and in vivo. Prior studies have identified benzoxaboroles that act on mRNA polyadenylation in P. falciparum (13), and genetic evidence supports a similar target in Toxoplasma gondii (14). Related benzoxaboroles are potent inhibitors of C. parvum growth in an in vitro model and calf model of cryptosporidiosis (15).…”
mentioning
confidence: 95%
“…This class of imidazopyrazines inhibits phosphatidylinositol 4 kinase (PI4K) in Plasmodium falciparum (12), an activity that may explain its potent ability to control C. parvum growth in vitro and in vivo. Prior studies have identified benzoxaboroles that act on mRNA polyadenylation in P. falciparum (13), and genetic evidence supports a similar target in Toxoplasma gondii (14). Related benzoxaboroles are potent inhibitors of C. parvum growth in an in vitro model and calf model of cryptosporidiosis (15).…”
mentioning
confidence: 95%
“…CPSF3, an essential component for converting heteronuclear RNA to mRNA, is associated with cellular stress response 1 protein-mediated cell death [87] and also can be designed as an novel target for control toxoplasmosis[88]. The RNA binding protein FXR1 is a critical regulator of post-transcriptional gene expression in differentiation, development and immunity [89,90].…”
Section: Discussionmentioning
confidence: 99%
“…However, among the changes in resistant lines was an amplification in the gene copy number of the RNA cleavage and polyadenylation specificity factor subunit 3 (CPSF3) [93]. Subsequently, CPSF3 was identified as a target for benzoxaboroles in apicomplexan parasites Plasmodium [93] and Toxoplasma [94]. Based on this observation, and the fact that metabolomics experiments had revealed a profound change in the methionine metabolism [95] that might have been related to RNA processing defects, particularly given the multi-methylation of the spliced leader sequence used in trans-splicing in trypanosomes, the effect of over-expression of CPSF3 on sensitivity to the related benzoxaborole, AN7973, was tested [96].…”
Section: Acoziborole: Mode Of Action and Resistance Riskmentioning
confidence: 99%